Using mixed methods to understand spatio-cultural process in the informal settlements: Case studies from Islamabad, Pakistan - Shafqat, Ramisa; Marinova, Dora (2022)
A mixed-methods approach is used to understand the human factors defining cultural heritage in two informal settlements in Islamabad, Pakistan, namely France Colony and Mehr Abadi. The methodology applied is based on spatial investigation within a placemaking framework to create a visual representation of the neighborhoods, and grounded theory to explore the experiences and memories of their inhabitants through verbal communication. A combination of techniques, including transect walks, photography, and on-site interviews, allows us to map the tangible and intangible elements of the informal settlements. Cultural characteristics are identified as essential in the spatio-cultural processes occurring in the informal settlements. The study concludes that cultural dilapidation happens because of obstructions in the processes translating intangible heritage into tangible space. Appropriate policy interventions are suggested to minimize the loss of rural heritage transfer to informal settlements within the urban fabric of Islamabad.